2022
DOI: 10.1186/s12889-022-13682-z
|View full text |Cite
|
Sign up to set email alerts
|

The willingness of parents to vaccinate their children younger than 12 years against COVID-19: a cross-sectional study in Malaysia

Abstract: Background The initiation of a new drug, for instance, the coronavirus disease 2019 (COVID-19) vaccine in children could be a source of major concern for parents. This study aims to determine the willingness of parents in Malaysia to vaccinate their children younger than 12 years against COVID-19. Methods An online cross-sectional survey was conducted nationwide in Malaysia from August 29, 2021, to October 17, 2021. Parents with children younger th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
18
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 54 publications
6
18
5
Order By: Relevance
“…Issues regarding confidence in the vaccine efficacy and safety, quality uncertainty, and lack of adequate available information were cited as the contributing factors to the high level of PVh in those studies [ 15 , 16 , 22 , 23 ]. Although some recent studies conducted in the United States [ 26 , 27 ], Malaysia [ 28 ], and South Korea [ 29 ] found that PVh prevalences were considerably lower than our finding (15–28.9%), the above contributing factors of PVh were still indicated [ 26 28 ].…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…Issues regarding confidence in the vaccine efficacy and safety, quality uncertainty, and lack of adequate available information were cited as the contributing factors to the high level of PVh in those studies [ 15 , 16 , 22 , 23 ]. Although some recent studies conducted in the United States [ 26 , 27 ], Malaysia [ 28 ], and South Korea [ 29 ] found that PVh prevalences were considerably lower than our finding (15–28.9%), the above contributing factors of PVh were still indicated [ 26 28 ].…”
Section: Discussioncontrasting
confidence: 97%
“…Those results indicated that the direct experience of the parents with their COVID-19 vaccination was one of the key factors influencing PVh. This hypothesis was supported by previous studies which found that there was an inverse relationship between COVID-19 vaccination history of the parents and PVh [ 15 , 16 , 28 , 30 ]. Therefore, a campaign to create a positive attitude towards vaccination for themselves and increase the rate of COVID-19 vaccination among parents, in addition to the promotion of their child’s vaccination should be conducted.…”
Section: Discussionsupporting
confidence: 78%
“…
Parental vaccine hesitancy is present even among healthcare workers (HCWs). While HCWs are generally more likely to vaccinate their children than the general population, parental vaccine hesitancy exists even among this group [6,7]. A June 2021 poll of over 2,000 HCWs in the United States reported that only half of the registered and licensed practical nurses plan to vaccinate their children under 12 years immediately after vaccines become available [8].
…”
mentioning
confidence: 99%
“…The presence of parental vaccine hesitancy among nurses might negatively affect their ability to provide impartial advice to patients regarding vaccination decisions for their families. Vaccine hesitancy among nurses also interferes with the mission of public health officials to increase vaccination rates among children.Second, existing studies examined parents' attitudes toward a hypothetical vaccine only [6,[16][17][18]. This is…”
mentioning
confidence: 99%
See 1 more Smart Citation